Born of Clay Ceramics from the National Museum of the American Indian - Solis, Felipé (2005)
The museum's holdings are rich in examples of Native ceramics from throughout the Western Hemisphere, stretching across forty centuries to the present day. In this book, four scholars introduce important and little-known ceramic figures and vessels representing the cultures of the Andes, Mexico, the American Southwest, and the eastern United States. Extensively illustrated with beautiful new photographs of objects from the museum's collections, including many pieces published here for the first time, Born of Clay brings curatorial and Native artistic perspectives together to present a lively and concise introduction to Native American ceramics.